Affibody-Modified Gd@C-Dots with Efficient Renal Clearance for Enhanced MRI of EGFR Expression in Non-Small-Cell Lung Cancer - Wu Y (Dove Medical Press, 2020)
Yongyi Wu,1,2,* Haoxiang Li,1,2,* Yuling Yan,1,2,* Kai Wang,1,2 Yongna Cheng,1,2 Yangyang Li,1,2 Xinyuan Zhu,3 Jin Xie,4 Xilin Sun1,2 1NHC and CAMS Key Laboratory of Molecular Probe and Targeted Theranostics, Molecular Imaging Research Center (MIRC), Harbin Medical University, Harbin, Heilongjiang, 150028, People’s Republic of China; 2TOF-PET/CT/MR Center, The Fourth Hospital of Harbin Medical University, Harbin, Heilongjiang 150028, People’s Republic of China; 3School of Chemistry and Chemical Engineering, Shanghai Key Laboratory for Molecular Engineering of Chiral Drugs, Shanghai Jiao Tong University, Shanghai 200240, People’s Republic of China; 4Department of Chemistry and Bio-Imaging Research Center, The University of Georgia, Athens, Georgia 30602, USA*These authors contributed equally to this workCorrespondence: Xilin SunNHC and CAMS Key Laboratory of Molecular Probe and Targeted Theranostics, Molecular Imaging Research Center, Harbin Medical University, 766 Xiangan N Street, Songbei District, Harbin, Heilongjiang 150028, People’s Republic of ChinaFax +86-451-82576509Email sunxl@ems.hrbmu.edu.cnJin XieDepartment of Chemistry, University of Georgia, Athens, GA 30602, USAEmail jinxie@uga.eduPurpose: Gd-encapsulated carbonaceous dots (Gd@C-dots) have excellent stability and magnetic properties without free Gd leakage, therefore they can be considered as a safe alternative T1 contrast agent to commonly used Gd complexes. To improve their potential for cancer diagnosis and treatment, affibody-modified Gd@C-dots targeting non-small-cell lung cancer (NSCLC) EGFR-positive tumors with enhanced renal clearance were developed and synthesized.Materials and Methods: Gd@C-dots were developed and modified with Ac-Cys-ZEGFR:1907 through EDC/NHS. The size, morphology, and optical properties of the Gd@C-dots and Gd@C-dots-Cys-ZEGFR:1907 were characterized. Targeting ability was evaluated by in vitro and in vivo experiments, respectively. Residual gadolinium concentration in major organs was detected with confocal imaging and inductively coupled plasma mass spectrometry (ICP-MS) ex vivo. H&E staining was used to assess the morphology of these organs.Results: Gd@C-dots with nearly 20 nm in diameter were developed and modified with Ac-Cys-ZEGFR:1907. EGFR expression in HCC827 cells was higher than NCI-H520. In cell uptake assays, EGFR-expressing HCC827 cells exhibited significant MR T1WI signal enhancement when compared to NCI-H520 cells. Cellular uptake of Gd@C-dots-Cys-ZEGFR:1907 was reduced, when Ac-Cys-ZEGFR:1907 was added. In vivo targeting experiments showed that the probe signal was significantly higher in HCC827 than NCI-H520 xenografts at 1 h after injection. In contrast to Gd@C-dots, Gd@C-dots-Cys-ZEGFR:1907 nanoparticles can be efficiently excreted through renal clearance. No morphological changes were observed by H&E staining in the major organs after injection of Gd@C-dots-Cys-ZEGFR:1907.Conclusion: Gd@C-dots-Cys-ZEGFR:1907 is a high-affinity EGFR-targeting probe with efficient renal clearance and is therefore a promising contrast agent for clinical applications such as diagnosis and treatment of NSCLC EGFR-positive malignant tumors.Keywords: Gd@C-dots, EGFR, MRI, nanoparticles, efficient renal clearance